2017
DOI: 10.1213/ane.0000000000001984
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative “Analgesia Nociception Index”–Guided Fentanyl Administration During Sevoflurane Anesthesia in Lumbar Discectomy and Laminectomy: A Randomized Clinical Trial

Abstract: Patients receiving intraoperative ANI-guided fentanyl administration during sevoflurane anesthesia for lumbar discectomy and laminectomy demonstrated decreased pain in the recovery room, likely as a result of more objective intraoperative fentanyl administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 42 publications
5
63
1
5
Order By: Relevance
“…In addition, methodological flaws (for instance, the report fails to detail data collection and blinding procedures) reduce the quality of evidence of this study. The studies of Szental et al and Upton et al found no differences in opioid use during anesthesia, however opioid consumption was not the primary outcome of both studies and the use of morphine for intraoperative analgesia may not have been an ideal choice [23,24]. Regarding other endpoints, only Upton et al, found lower pain scores in ANI guided patients after lumbar discectomy or laminectomy (mean difference first 90 min postoperative 1.3 NRS points, p = 0.01; see Table 2) [24].…”
Section: Analgesia Nociception Index (Ani)mentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, methodological flaws (for instance, the report fails to detail data collection and blinding procedures) reduce the quality of evidence of this study. The studies of Szental et al and Upton et al found no differences in opioid use during anesthesia, however opioid consumption was not the primary outcome of both studies and the use of morphine for intraoperative analgesia may not have been an ideal choice [23,24]. Regarding other endpoints, only Upton et al, found lower pain scores in ANI guided patients after lumbar discectomy or laminectomy (mean difference first 90 min postoperative 1.3 NRS points, p = 0.01; see Table 2) [24].…”
Section: Analgesia Nociception Index (Ani)mentioning
confidence: 97%
“…A total of 1045 patients were studied, with 520 receiving an intervention compared to 526 treated according to routine clinical care. Care guided using the SPI was evaluated in six studies [16][17][18][19][20][21] followed by the ANI in three studies [22][23][24]. The NOL, pupillometry and the beat-to-beat cardiovascular depth of anesthesia index (CARDEAN 2.0) were evaluated in single studies [15,25,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCTs that tested systemic lidocaine, ketorolac, and NSAIDs (tenoxicam) led to controversial results . Upton et al found that fentanyl administered while maintaining an Analgesia Nociception Index of > 50 with boluses of 50 μg (in patients < 50 years of age) or 25 μg (in patients > 50 years of age) was more effective than the “classic” administration …”
Section: Resultsmentioning
confidence: 99%
“…the analgesia nociception index (ani) has been introduced to assess intraoperative pain and titrate analgesic administration. 129 theearth et al evaluated the performance of the index in 60 adult patients who underwent elective supra-tentorial tumor surgery and received scalp block or incision-Review just found insufficient evidence that administration of melatonin improves the quality and quantity of sleep in critically ill patients due to differences in sedation protocols and methodological issues. 116 Ferreira albuquerque costa et al conducted a systematic review on perioperative ultrasound applied to diagnosis and decision-making in anesthesia.…”
Section: Postoperative Analgesiamentioning
confidence: 99%